Diabetes mellitus is a potential risk factor for aseptic loosening around hip and knee arthroplasty - Yi Deng; Paul N Smith; Rachel W Li (BMC Musculoskeletal Disorders, 2023)
Abstract Background Aseptic loosening is a leading cause of revision following total hip and knee arthroplasty which is caused by chronic inflammation around the prosthesis. Diabetes mellitus causes systemic inflammatory changes which could increase the risk of aseptic loosening. This study investigated the association between diabetes mellitus and aseptic loosening around hip and knee arthroplasty. Methods A case-control study was conducted at a single arthroplasty centre over the seven-year period of January 2015 to December 2021. Cases were defined as any adult patient undergoing revision hip or knee arthroplasty for aseptic loosening. Controls were randomly selected patients undergoing primary total hip or knee arthroplasty during the same period at a 1:4 ratio. Risk factors were compared between the two groups. Results A total of 440 patients were included in our study – 88 in the aseptic loosening group and 352 patients in the control group. The odds of having diabetes mellitus in the aseptic loosening group was 2.78 (95%CI 1.31–5.92, P = 0.01). Other risk factors were not significantly different between the two groups. Conclusions The incidence of diabetes mellitus is significantly greater in patients undergoing revision arthroplasty for aseptic loosening. Further research is required to explore whether this association is indeed causative.